2019
DOI: 10.1007/bf03544445
|View full text |Cite
|
Sign up to set email alerts
|

The lack of males due to illegal trapping is causing polygyny in the globally endangered Yellow Cardinal Gubernatrix cristata

Abstract: We present breeding data from the southernmost populations of the globally “Endangered” Yellow Cardinal Gubernatrix cristata in Argentina, confirming the presence of current breeding populations in the region. We monitored a family group in a nesting territory composed of one male and three females throughout the breeding season 2017–2018. We found a low nest success and productivity, probably associated with the lower contribution of the male, since it was attending three reproductive females simultaneously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 11 publications
0
19
1
1
Order By: Relevance
“…Domínguez et al (2015) conducted their study prior (2011)(2012) to ours (2013)(2014)(2015), so we cannot determine whether the differences found were related to temporal or spatial factors. Additionally, we have already reported cooperative breeding in the Brazilian population (Beier et al 2017), which was not reported in other populations (Domínguez et al 2015, Segura et al 2019. We found higher frequency (67%) and intensity (~2 eggs/parasitized nest) of brood parasitism by cowbirds than in Argentina (33%, 1 egg/parasitized nest; Domínguez et al 2015).…”
Section: Discussioncontrasting
confidence: 48%
“…Domínguez et al (2015) conducted their study prior (2011)(2012) to ours (2013)(2014)(2015), so we cannot determine whether the differences found were related to temporal or spatial factors. Additionally, we have already reported cooperative breeding in the Brazilian population (Beier et al 2017), which was not reported in other populations (Domínguez et al 2015, Segura et al 2019. We found higher frequency (67%) and intensity (~2 eggs/parasitized nest) of brood parasitism by cowbirds than in Argentina (33%, 1 egg/parasitized nest; Domínguez et al 2015).…”
Section: Discussioncontrasting
confidence: 48%
“…Solving the dichotomy between opportunistic or selective poaching has profound conservation implications, since the overexploitation of preferred species may be causing their decline, pushing their populations toward regional [11,58] and global [84] extinctions. Several lines of evidence show that any form of harvesting (including legal fishing and hunting) is selective toward individuals of a certain sex, size, morphology, or behavior, with long-term population and evolutionary consequences [93][94][95][96][97][98][99]. However, to our knowledge, the hypothesis of selective harvest at the community level (i.e., on species with particular characteristics over others ) has not yet been properly tested, mainly due to the difficulty of assessing their availability in the wild.…”
Section: Further Prospects For Assessing Selective Harvestingmentioning
confidence: 99%
“…2015, Segura et al . 2019). The ranch contains thorny shrubland forests with different vegetation densities, dominated by calden mesquite Prosopis caldenia , within the Espinal ecoregion (Morello et al 2012), covering a total area of 1,320 ha.…”
Section: Methodsmentioning
confidence: 99%
“…The study took place in a private livestock ranch in La Pampa province, Argentina (36˚48'S; 64˚37'W) from early October to late December 2019, covering almost the entire breeding season of the species (late September-early January; Domı ´nguez et al 2015, Segura et al 2019. The ranch contains thorny shrubland forests with different vegetation densities, dominated by calden mesquite Prosopis caldenia, within the Espinal ecoregion (Morello et al 2012), covering a total area of 1,320 ha.…”
Section: Study Sitementioning
confidence: 99%